Analysis of the Relationship between Leadership Style and Work Motivation to Employee Loyalty at PT Anugerah Putra Langkat - Bagas Indrianto Prasetio; M. Chaerul Rizky; Agita Trianto; Ahmad Ihsan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Employee loyalty constitutes a pivotal determinant in the triumph of an organization, particularly amidst the escalating intensity of modern business rivalry. PT Anugerah Putra Langkat, an enterprise situated in North Sumatra, grapples with the predicament of preserving competent personnel and cultivating enduring organizational allegiance. An appropriate leadership paradigm accompanied by optimal motivational stimuli is presumed to exert a considerable impact on the magnitude of employee devotion within the company. The present research aimed to identify the correlation between leadership orientation and occupational motivation toward employee loyalty at PT Anugerah Putra Langkat. Employing a quantitative methodology with both descriptive and explanatory research frameworks, the investigation encompasses the entire workforce of 156 individuals, with a sampling cohort of 85 respondents selected through a saturated sampling technique. The findings reveal that, individually, leadership style exerts a constructive and statistically significant influence on occupational loyalty. Likewise, work motivation demonstrates a positive and meaningful correlation with employee allegiance. Collectively, these two variables exhibit a conjoint and substantial impact on overall job loyalty.